Classes of Meromorphic Functions Defined by the Hadamard Product - J. Dziok (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to introduce new classes of meromorphic functions with varying argument of coefficients defined by means of the Hadamard product (or convolution). Several properties like the coefficients bounds, growth and distortion theorems, radii of starlikeness and convexity, and partial sums are investigated. Some consequences of the main results for well-known classes of meromorphic functions are also pointed out.